THE EFFECT OF CLOPIDOGREL ON REPERFUSION IN ACUTE ST ELEVATING MYOCARDIAL INFARCTION - Akbulut, M.; Polat, V.; Bilen, M.; Ozbay, Y.; Kutlu, M.; Baydas, A.; Altas, Y. (Elsevier Ireland Ltd, 2008)
[Abstract Not Available]